The concept of 'mechanosis' by Jalal Al-e Ahmad : a critical study from the Islamic perspective - Muhammad Hafizuddin bin Abu Hasan (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
Jalāl Āl-e Ahmad's concept of 'mechanosis' in his masterpiece, Occidentosis: A Plague from the West was examined through a library and qualitative research to determine its relevance with Islamic teaching, amid the Iranian dependency of the West. The thoughts of selected Occident philosophers of technology were analyzed in finding the influence of Jalāl Āl-e Ahmad's 'mechanosis' in mechanization. Jalāl Āl-e Ahmad's argument of the negative impact of Western invasion through technology and machine stressed the weak side of dependency. The researcher found the relevant relationship between Jalāl Āl-e Ahmad's 'mechanosis' and the Islamic perspective towards technological advancement and total dependent of Iran, in particular, and The Third World countries, in general, to the Western power. This study was significant in providing the conceptual boundaries between developing technology based on Western paradigm and enhancing country's own capability in applying scientific knowledge for machine and technology.